IRAP Drives Ribosomal Degradation to Refuel Energy for Platelet Activation during Septic Thrombosis - Baichuan Xu; Xianpeng Ye; Kangfu Sun; Liang Chen; Zhaoyang Wen; Qigang Lan; Jun Chen; Mo Chen; Mingqiang Shen; Song Wang; Yang Xu; Xi Zhang; et al. (Advanced Science)
Abstract Platelets play crucial roles in multiple pathophysiological processes after energy‐dependent activation. It is puzzling how such a small cellular debris has abundant energy supply. In this study, it is shown that insulin‐regulated aminopeptidase (IRAP), a type II transmembrane protein, is a key regulator for platelet activation by promoting energy regeneration during septic thrombosis. Through interaction with certain endosome membrane proteins, IRAP can not only promote granule release, but also facilitate lysosomal degradation of theoretically discarded ribosomes in an mTORC1‐ and S‐acylation‐dependent manner in activated platelets. Plentiful amino acids obtained from IRAP‐mediated ribophagy are recruited to aerobic glycolysis and then promote energy metabolism reprogramming, thereby producing abundant energy for platelet life extension and prolonged activation. Consequently, targeted blocking IRAP can dramatically alleviate platelet hyperactivation and septic thrombosis.